Village Asset Management Innovations Through Application-Based Systems: Inovasi Pengelolaan Aset Desa Melalui Sistem Berbasis Aplikasi - Maarif , Mochammad Syaroni; Sukmana, Hendra (Indonesian Journal of Law and Economics Review, 2024)
Background: Effective asset management in rural areas is vital for transparency and accountability in village governance. Specific Background: This study examines the management of village assets through the Village Asset Management System (SIPADES). Knowledge Gap: Despite its implementation, many villages struggle with systematic asset management, raising concerns about regulatory compliance and efficiency. Aims: The research aims to analyze current asset management practices using SIPADES and identify challenges faced by local administrators. Results: Findings reveal that while SIPADES offers a structured framework, issues with data collection and adherence to regulations hinder its effectiveness. Novelty: This study highlights the need for improved training for local operators in digital asset management. Implications: Enhancing administrators' capacity in SIPADES can lead to better asset management outcomes, promoting accountability in rural governance and aligning practices with national regulations, crucial for sustainable development. Highlights : Structured Framework: SIPADES provides a systematic approach to asset management in villages. Training Needs: Enhanced training for local administrators is essential for effective system utilization. Regulatory Alignment: Addressing compliance issues is crucial for promoting accountability and sustainable development. Keywords: asset management, rural governance, SIPADES, regulatory compliance, transparency